COMPARISON OF THE RADIATION SENSITIVITY OF THE BREAST CANCER CELL LINE MCF7 AND HUMAN ADIPOSE-DERIVED STEM CELLS - Michaelidesová, Anna; Vachelová, Jana; Cupal, Lukáš; Konířová, Jana; Brabcová, Kateřina Pachnerová; Bačáková, Lucie; Vandrovcová, Marta; Davídková, Marie (Radiation protection dosimetry, 2019)
A comparison between breast cancer cell line MCF7 and human adipose-derived stem cells (ADSC) after irradiation by the same doses of megavoltage X-rays was performed. The cell growth, the induction of apoptosis and the expression of selected genes were analyzed. Irradiated MCF7 related to its control sample grows slower than ADSC and it undergoes apoptosis in much higher levels than ADSC. This was confirmed by real-time polymerase chain reaction as well, where the expression of apoptotic genes was found to be considerably higher for MCF7 than for ADSC. From the results of this project, it could be stated that MCF7 is more radiosensitive than ADSC.
Keywords: MFC-7 buňky; kmenové buňky; apoptóza; MCF-7 Cells; proliferace buněk; Radiation Tolerance; Stem Cells; tukové buňky; Adipocytes; lidé; tolerance záření; Cell Proliferation; Apoptosis; Humans